INCREASING YOUTH KNOWLEDGE IN HANDLING MENSTRUAL PAIN IN STUDENTS OF THE ISLAMIC JUNIOR HIGH SCHOOL OF AL-MU’AWANAH, MINGGIR, SIDOARJO - Agus Sulistyowati; Edgina Fidela Kusuma; Ria Dinia; Lela Anggarini; Junaidah Anugraheni; Elisabeth Febi Fuankali; Puji Yudha Raka Siwi (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Health promotion activities about the first aids during menstrual pain in the Islamic Junior High School of Al-Mu'awanah, Minggir, Sidoarjo is one form of community service in the form of counseling aimed at increasing children's knowledge about how the first treatment during menstrual pain which is an event of blood loss from the womb of a woman when she reaches baligh. The implementation of these activities on November 13, 2019 took place at the Islamic Junior High School of Al-Mu'awanah, Minggir, Sidoarjo. The target is all of the students of the Islamic Junior High School of Al-Mu'awanah, Minggir, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 2 weeks before the activity is carried out, starting from determining the theme of counseling to submitting licensing to the parties concerned. As a form of evaluation, the activity was attended by 26 students of VII grade of the Islamic Junior High School of Al-Mu'awanah, Minggir, Sidoarjo, participants took part in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly. Keywords: Youth knowledge, menstrual pain, health promotion of first aids.